Durable Peace : Challenges for Peacebuilding in Africa. - Ali, Taisier, M. (University of Toronto Press, 2004)
With Durable Peace, Taisier M. Ali and Robert O. Matthews have brought together leading scholars to discuss the experiences of ten African countries in recovering from violent civil war.